2014 7th Advanced Satellite Multimedia Systems Conference and the 13th Signal Processing for Space Communications Workshop (ASM 2014
DOI: 10.1109/asms-spsc.2014.6934518
|View full text |Cite
|
Sign up to set email alerts
|

Contact Graph Routing enhancements for delay tolerant space communications

Abstract: In this paper we present two enhancements to Contact Graph Routing (CGR), a Delay-/ Disruption-Tolerant Networking routing algorithm developed by NASA JPL for space environments with predetermined connectivity schedules, such as Interplanetary communications and LEO satellite systems. The first enhancement, CGR-ETO, aims to improve the accuracy of predicted bundle delivery time by considering the available information on queueing delay. The second, the Overbooking Management, aims to proactively handle contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…Along with the progress of these two area, many variants and enhanced edition are published by with different aims and different solution [7,8,12,13]. Although these enhanced edition might surmount base edition in some custom environment in some specified target, the comparing between algorithms of different design aims would be meaningless and illogical, which is the reason leads us to choose the base edition of these two algorithm for simulation.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations
“…Along with the progress of these two area, many variants and enhanced edition are published by with different aims and different solution [7,8,12,13]. Although these enhanced edition might surmount base edition in some custom environment in some specified target, the comparing between algorithms of different design aims would be meaningless and illogical, which is the reason leads us to choose the base edition of these two algorithm for simulation.…”
Section: Purposementioning
confidence: 99%
“…As noted in this paper [13], CGR has its own problem, the exhaust search and pick one scheme, of which picking one operation is presented as CGR-Forward Decision affects the routing result. That is to say, in this simulation, we use a naive forward decision with no throughput optimal, which is the factor leads to the result that CGR perform no better than TEG when overhead reach its max throughput.…”
Section: Shortcomings Of Cgrmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, in 2014, authors studied the implementation of temporal route lists as a mean to minimize CGR executions [57]. In the same year, Bezirgiannidis et al [58] suggested to monitor transmission queues within CGR as they increase the earliest transmission opportunity (CGR-ETO). On the same paper, a complementary overbooking management innovation enables proactive reforwarding of bundles whose place in the outbound queue was taken by subsequent higher priority traffic.…”
Section: Contact Graph Routingmentioning
confidence: 99%
“…is not empty then (25) procedure (the overbooking management procedure defined in [58] aims at reordering the local outbound queues when bundles with higher priorities replace less urgent bundles; since in this work we assume all bundles have the same priority, this procedure is not described) (Algorithm 1, lines (25) to (26)). However, if the CGR Forward fails to find a suitable neighbor, the bundle is stored in special memory space called limbo waiting for a higher level process to either erase it or retry a new forwarding later (e.g., after a contact plan update).…”
Section: Contact Graph Routingmentioning
confidence: 99%